Komparasi Representasi Identitas Visual Kemaritiman Kota Palembang dan Kota Makassar - Yosef Yulius; Alit Kumala Dewi; I Wayan Mudra; Erwan Suryanegara; Arini Chelsea Putri; Faftah Talulah Wardoyo (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
This study examines the representation of maritime visual identity in the cities of Palembang and Makassar. The study is motivated by the gap between Palembang’s strong historical maritime legacy rooted in the Sriwijaya civilization and the relatively weak representation of maritime identity in the public sphere, while Makassar demonstrates a more consistent maritime identity through the use of the Pinisi symbol. To understand this difference, the study compares visual characteristics, the relationship between symbols and maritime identity, and the consistency of symbolic reproduction in both cities. This study aims to analyze the visual representation of maritime identity in Palembang and Makassar and to identify differences in the strength of the visual identities formed. A comparative qualitative approach was employed. Data were collected through visual observation, documentation, and literature review, and were analyzed through the identification and classification of visual elements, interpretation of meaning, and comparison between the two cities. The findings reveal that the visual representation of Sriwijaya in Palembang remains fragmented, lacks a dominant visual symbol, and has not yet developed into a consistent visual identity system. In contrast, the Pinisi symbol in Makassar is continuously reproduced across various visual media, forming a maritime identity that is more dominant, consistent, and easily recognizable. This study concludes that the strength of maritime visual identity is determined not only by historical and cultural heritage but also by the presence of distinctive symbols and the consistency of their visual reproduction in building collective recognition in the public sphere